STUDENTS’ PERCEPTIONS OF ICE-BREAKING ACTIVITIES USED BY ENG-LISH TEACHERS IN TEACHING PROCESS AT SMAN 10 PEKANBARU - Wilastri Ayunda; Mahdum; Muhammad Syarfi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores students’ perceptions of ice-breaking activities implemented by English teachers in the teaching process at SMAN 10 Pekanbaru. A quantitative descriptive design was employed, and data were collected through a questionnaire. The results indicate that students generally held positive perceptions of ice-breaking activities, particularly regarding their role in creating a supportive and engaging classroom atmosphere. These activities were also perceived as effective in reducing anxiety, fostering comfort, and encouraging active participation and interaction among students. However, their influence on focus, concentration, and comprehension of lesson material was considered moderate, suggesting that ice-breaking activities serve primarily as motivational and social supports rather than direct tools for enhancing academic understanding. Overall, ice-breaking activities are regarded as beneficial supplementary strategies that can promote a positive classroom atmosphere, enhance students’ emotional readiness, and support increased engagement in English learning.